2011
DOI: 10.1111/j.1365-2036.2011.04775.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the effects of amitriptyline on drinking capacity and symptoms in patients with functional dyspepsia, a double-blind placebo-controlled study

Abstract: SUMMARY BackgroundFunctional dyspepsia is one of the most prevalent (15-40%) functional gastrointestinal disorders. Antidepressants such as amitriptyline are often used in these patients, but clinical studies are currently lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 52 publications
(69 reference statements)
1
64
0
Order By: Relevance
“…A systematic review ( 72 ) identifi ed 13 RCTs evaluating psychotropic drugs in FD. Th ere were three trials (126)(127)(128) involving 339 FD patients comparing TCAs with placebo. Th ere was a statistically signifi cant eff ect in reducing dyspepsia symptoms (RR=0.74; 95% CI=0.61-0.91) with an NNT of six (95% CI=6-18).…”
Section: Conditional Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…A systematic review ( 72 ) identifi ed 13 RCTs evaluating psychotropic drugs in FD. Th ere were three trials (126)(127)(128) involving 339 FD patients comparing TCAs with placebo. Th ere was a statistically signifi cant eff ect in reducing dyspepsia symptoms (RR=0.74; 95% CI=0.61-0.91) with an NNT of six (95% CI=6-18).…”
Section: Conditional Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…22 A recent trial of amitriptyline for FD used maximal satiety as an outcome parameter when drinking 100 mL of a nutrient drink at every minute. 16 However, amitriptyline did not affect the subjects' drinking capacity or the postprandial symptoms evoked by the drink test, although the total clinical symptom score and nausea were reduced after treatment. The NDT has several advantages in clinical trials of FD treatments, including its noninvasiveness, easy performance, and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,14,15 A NDT was used in a clinical trial of amitriptyline, although amitriptyline did not affect the drinking capacity of the subjects or the postprandial symptoms evoked by the drink test in FD patients. 16 It is not determined whether the results of drink tests can reflect response of prokinectic drug. Itopride is currently available in Korea and Japan, indicated for the treatment of FD.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study argue against the use of this class of agents in FD, but this should not be extrapolated to all psychotropics [37]. In fact, a smaller study in 38 patients showed benefit with amitriptyline over placebo in improving total symptom score and nausea [38]. More recently, a study in FD patients with weight loss and no anxiety or depression, showed that mirtazapine 15 mg in the evening for 8 weeks was superior to placebo in improving overall symptom score, early satiation, nutrient tolerance and weight recovery.…”
Section: Pharmacotherapymentioning
confidence: 99%